BUSINESS STRATEGIES OF MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) IN FACING COMPETITION IN THE DIGITAL ERA IN CITAMIANG DISTRICT, SUKABUMI CITY - Wahyudi, Muhamad Farhan; Danial, R.Deni Muhammad; Jhoansyah, Dicky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the ever-evolving digital era, businesses must face rapid and complex changes. New technologies, changing consumer behavior, and global challenges require business actors to have sound adaptation strategies. However, many Micro, Small, and Medium Enterprises (MSMEs) in Sukabumi City have not yet optimally utilized digital potential. Many still rely on traditional methods such as word-ofmouth marketing and physical sales. This highlights the digital divide among MSMEs that needs to be addressed through mentoring, digital training, and empowerment programs. Based on data and phenomena, the author used a qualitative research method. The author analyzed the issue related to social problems by implying important efforts, namely by asking questions to participants and collecting data that was then analyzed and interpreted using a descriptive approach, which can provide an overview of the focus of the author's research in the form of words. MSMEs that adapt to digital technology gain benefits such as increased competitiveness and market reach. However, they face obstacles such as costs, low technological understanding, and lack of policy support. Effective strategies to increase MSME competitiveness include digital marketing on social media, collaboration with marketplaces, digital literacy training, and product innovation. It is recommended to start developing a simple digital strategy.